(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
Selection of suitable packaging film is necessary to minimize the deteriorative changes of foods. Packaging films differ for different food products. Flexible packaging films are now widely used instead of hard packages for processed dry food products. In this study attempt has been made to select a suitable packaging film for dry coriander powder at ambient temperature. Three types of packaging films like heat sealable laminated aluminium foil, high density polythene (HDPE) and poly propylene (PP) were chosen. The changes in water activity, total ash, acid insoluble ash and consequent effect on sensory qualities like texture, colour, flavour and appearance of coriander powder were investigated at an interval of two months during one year storage period. Bangladesh J. Sci. Ind. Res. 42(1), 53-58, 2007